2019
DOI: 10.1029/2018gl081500
|View full text |Cite
|
Sign up to set email alerts
|

Magnetospheric Chorus, Exohiss, and Magnetosonic Emissions Simultaneously Modulated by Fundamental Toroidal Standing Alfvén Waves Following Solar Wind Dynamic Pressure Fluctuations

Abstract: Magnetospheric quasiperiodic whistler‐mode emissions have long been considered a consequence of the relaxation oscillation or the compressional ultralow‐frequency wave modulation. Here we experimentally demonstrate that the whistler‐mode chorus, exohiss, and magnetosonic emissions can be effectively modulated by the toroidal ultralow‐frequency waves. On 04 August 2017, the solar wind dynamic pressure fluctuations excited the fundamental toroidal standing Alfvén waves in the dayside magnetosphere. These regular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 98 publications
(224 reference statements)
0
11
0
1
Order By: Relevance
“…It has been demonstrated that ULF waves are able to modulate MS waves and generate rising (Boardsen et al., 2014) or falling tone features (N. Liu et al., 2019). The modulated MS waves have almost the same element period as the period of ULF waves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that ULF waves are able to modulate MS waves and generate rising (Boardsen et al., 2014) or falling tone features (N. Liu et al., 2019). The modulated MS waves have almost the same element period as the period of ULF waves.…”
Section: Discussionmentioning
confidence: 99%
“…Quasiperiodic rising and falling tone features are commonly observed for chorus (Li et al., 2011) and magnetosonic (MS) waves (Boardsen et al., 2014; N. Liu et al., 2019), and sometimes observed for electromagnetic ion cyclotron (EMIC) waves (Grison et al., 2018) and plume hiss (Shi et al., 2019; Su et al., 2018). However, the typical features of rising and falling tone ECH waves are still not well explored yet.…”
Section: Introductionmentioning
confidence: 99%
“…N. Liu et al. (2018, 2019) have demonstrated that MS waves can be modulated by the toroidal ultra‐low‐frequency waves following solar wind dynamic pressure fluctuations. MS waves can propagate both inward and outward with the wave vector k almost perpendicular to the ambient magnetic field B 0 (Chen & Thorne, 2012; Xiao et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al, 2011) have shown that MS waves can be excited by a proton ring distribution which is associated with the injection of energetic protons. N. Liu et al (2018Liu et al ( , 2019 have demonstrated that MS waves can be modulated by the toroidal ultra-low-frequency waves following solar wind dynamic pressure fluctuations. MS waves can propagate both inward and outward with the wave vector k almost perpendicular to the ambient magnetic field B 0 (Chen & Thorne, 2012;Xiao et al, 2012).…”
mentioning
confidence: 99%
“…Previous studies suggest that the whistler‐mode chorus waves are generally intensified (Fu, Cao, Mozer, et al., 2012; Fu, Cao, Zong, et al., 2012), while the intensity of plasmaspheric hiss waves decreases in the dayside and increases in the nightside (Liu, Su, Gao, Reeves, et al., 2017; Su et al., 2015; Yue et al., 2017) after the IP shock arrival. More recent studies indicate that plasmaspheric hiss waves also show patchy or modulated patterns under disturbed solar wind conditions or IP shock arrival (Chakraborty et al., 2021; Liu et al., 2019; Shang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%